Assigned versus assumed: Towards a contemporary, detailed understanding of subsidiary autonomy. Issue 6 (December 2017) - Cavanagh, Andrew; Freeman, Susan; Kalfadellis, Paul; Herbert, Kendall
Highlights: Further research is needed to explore the different types of autonomy. We create an integrative model of subsidiary autonomy based on two key types: assumed and assigned. Integrates agency theory, network theory, decision process perspective & bundling model. Abstract: This paper critically documents the rise of autonomy in subsidiary management literature, and develops an agenda for future research in this key area. Integrating and updating the seminal works of Paterson and Brock (2002) and Young and Tavares (2004), the paper begins with a critical review of subsidiary autonomy within the streams of subsidiary management literature. This leads to an assessment of the key contemporary issues requiring further investigation. These issues center around two key types of autonomy: assigned and assumed. We argue these types represent a more accurate, in-depth conceptualization of subsidiary autonomy, and also have significant implications for key related topics, including subsidiary development. This is depicted in an integrative model that draws upon agency theory, the network model of the MNE, the decision process perspective and the bundling model in presenting a revised view of subsidiary autonomy, and offers a basis for further research within the field.